Metal-free C–C coupling reactions with tetraguanidino-functionalized pyridines and light - Stang, Simone; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2014)
Herein we report on metal-free C–C coupling reactions mediated by the pyridine derivative 2,3,6,7-tetrakis(tetramethylguanidino)pyridine under the action of visible light. The rate-determining step is the homolytic N–C bond cleavage of the initially formed N-alkyl pyridinium ion upon excitation with visible light.
Gesehen am 31.07.2020